A Dialogic Approach to Interpretation of Iranian Heritage - Tolouashtiany, Shahin (Curtin University, 2020)
This thesis through Bakhtinian philosophy addresses extensive disagreement with official, monologic and monumentalist discourse of Mirase Farhangui, and widespread anxiety about loss of heritage fabric in Iran. It argues that Iranian heritage is polyphonic and answers the question of what is the best way to conceptualise Iranian heritage that would ensure a stronger conservation? It theorises Yadegar as a dialogic and familiar discourse, entrenched in Iranian culture, which provides better protection for Iranian heritage sites.